1989
DOI: 10.1042/bj2580157
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-reactive sites in collagens type I and type III. Evidence for separate adhesion and aggregatory sites

Abstract: The adhesion of human and rabbit platelets to collagens and collagen-derived fragments immobilized on plastic was investigated. Adhesion appeared to be independent of collagen conformation, since similar attachment occurred to collagen (type I) in monomeric form, as fibres or in denatured state. The adhesion of human platelets was stimulated to a variable degree by Mg2+, but rabbit platelet adhesion showed little if any dependence on this cation. Collagens type I, III, V and VI were all able to support adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 42 publications
(60 reference statements)
4
62
0
Order By: Relevance
“…Inhibition of the NCX by CBDMB caused a significant de- 3 min prior to the addition of collagen. b, relative percent change in collagen-induced platelet aggregation measured 2 min following the administration of collagen (10 g/ml) to platelets administered CBDMB (4 M) or EIPA (50 M) 3 min prior to the addition of collagen compared with the control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Inhibition of the NCX by CBDMB caused a significant de- 3 min prior to the addition of collagen. b, relative percent change in collagen-induced platelet aggregation measured 2 min following the administration of collagen (10 g/ml) to platelets administered CBDMB (4 M) or EIPA (50 M) 3 min prior to the addition of collagen compared with the control.…”
Section: Resultsmentioning
confidence: 99%
“…Collagen fibers are exposed to circulating platelets following injury to the vessel wall and play an important role in hemostasis through the creation of a physical barrier at the site of vascular damage, thereby limiting blood loss (2)(3)(4), and the stimulation of platelet activation, thereby recruiting additional platelets to the site of damage as well as consolidating the thrombus (4). The dual actions of collagen have been explained in the two-step model for activation, which suggests that adhesion and activation of platelets are mediated through the interaction of collagen with platelet integrin ␣ 2 ␤ 1 and glycoprotein VI, respectively (3, 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is difficult to test with collagen because of its numerous recognition sequences that can interact with different receptors. In the two-step, two-receptor model (39), which is the simplest version proposed for collagen-platelet interactions in primary hemostasis, it was suggested that the platelet binds through ␣ 2 ␤ 1 first and then is activated via interactions with GPVI/Fc␥. However, platelet activation via GPVI/Fc␥ may be necessary to modulate ␣ 2 ␤ 1 to allow it to bind to collagen.…”
Section: Figmentioning
confidence: 99%